DESIGNING COURSEBOOK FOR UNIVERSITY STUDENTS: ENGLISH FOR COLLEGIANS - Ira Irzawati; Yohanes Maria Restu Dian Raharjo; Tasya Hasan (Esteem Journal of English Education Study Programme, 2023)
The aim of this research is to design a coursebook for teaching English as a university compulsory subject. This research employed a Research and Development study that involves four English lecturers and eighty freshmen as the participants. Interviews and questionnaires were used as instruments to collect the data. The qualitative data were analyzed by using the adapted Miles and Huberman Model. Meanwhile, the quantitative data were analyzed by using a simple percentage analysis. At the end of this research, an English Coursebook, English for Collegian, has been finally completed. This book covers 14 units and each unit consists of seven main parts that accommodate comprehensive learning activities for each meeting. It is expected that this research brings fruitful impacts, especially in accommodating lecturers and students’ needs, improving students’ learning achievement, and boosting lecturers’ motivation to create teaching material.